Characterizing stakeholders in cancer primary prevention in European countries: an exploration of challenges and opportunities using a penta-helix framework - Luis Roxo; Luis Roxo; Luis Roxo; Ana Santos; Charis Girvalaki; Marius Geantă; 4P-CAN WP2 study team; Mafalda Sousa-Uva; Mafalda Sousa-Uva; Mafalda Sousa-Uva; Mirjana Babamova; Adriana Boată; et al. (Frontiers in Public Health)
ObjectivesCancer incidence has been increasing in Europe, with stark disparities between Western and Eastern regions. Cancer primary prevention (CPP) is a cost-effective strategy tackling lifestyle and risk factor exposure, but its implementation goes beyond the actions of the governments. This study aims to characterize stakeholders’ role in CPP, using a penta-helix approach, with the objective of shedding a new light in the Iron Curtain of Cancer Cases.MethodsWe followed a mixed-methods approach, with quantitative and qualitative data from CPP stakeholders from the public sector, academia/research, private sector, media and civil society. Snowball sampling was used to distribute a survey where participants (n = 110) were asked which sector was the main driver of change, the most proactive and the most influential. Purposive sampling was used for semi-structured interviews (n = 33), where stakeholders were asked about their CPP activities, motivations, barriers and opportunities, and the role of other sectors. Countries were coded as Western or Eastern. Descriptive analysis was used for quantitative data, while thematic analysis was used for qualitative data.ResultsThe public sector is viewed as the main driver of change, and the most proactive and influential in both Western and Eastern Europe. However, Eastern European countries emphasize the role of other sectors in CPP more strongly. Thematic analysis identified key roles and themes for the public sector (Strategy: “Looking after citizen’s health,” “Making the system work,” “Operational Engagement”), academia/research (Knowledge: “Scientific credibility,” “Diversity of approaches,” “Getting out of the lab,” “Life in academia/research”), private sector (Responsibility: “Profit-oriented,” “Resources and operational activities,” “Ethics and responsibility”), media (Dissemination: “Capacity to reach people,” “Diversity and scope,” “Information and dissemination”) and civil society (Engagement: “Proximity to people,” “Advocacy and voice,” “Do what others do not do”). Although no meaningful differences were identified between Western and Eastern countries, the results highlight opportunities for Eastern countries to reduce regional disparities.ConclusionOverall, results point to the complementary role of the sectors, emphasizing that involving different stakeholders and promoting adequate collaborations between them is crucial to unravel the full potential of CPP.